Alcohol Exposure While Serving in the United States Military - Agius, Marie (East Carolina University, 2017)
Over the past 30 years, alcohol use, misuse, and alcohol related problems have increased among military personnel. Researchers have tracked the rates of alcohol misuse and alcohol related problems among military personnel, but few have sought to understand alcohol exposure in the military. To fill this gap, the current study sought to understand the experience of alcohol exposure for active duty military personnel through a qualitative phenomenological design. Semi-structured interviews with participants were used to collect data. The grand tour question that guided this study was: How do active duty enlisted military personnel experience exposure to alcohol? Related sub-questions that directed the study included: 1. In what ways are active duty, enlisted military personnel exposed to alcohol during their enlistment period(s)? 2. How do active duty, enlisted military personnel describe their experiences with alcohol exposure? 3. In what ways, if any, does the military intrinsic and extrinsic cultures contribute to the use, misuse, and/or abuse of alcohol among active duty, enlisted military? Participant responses revealed three major themes that reflected their lived experiences of alcohol exposure during their military careers. These themes were drinking behaviors, military culture, and potential outcomes. Implications for counselor education, counseling service providers, military personnel, and future research are discussed.
Keywords: Phenomenology; Military Personnel; Alcohol Drinking; United States; Ethanol